Primary and Ipilimumab-induced Hypophysitis: A Single-center Case Series. (1st October 2020) - Atkins, Paul; Ur, Ehud
ABSTRACT: Purpose: To present a case series of primary and immunotherapy-related secondary hypophysitis. Methods: A single-center retrospective chart review was performed at the University of British Columbia, Vancouver, Canada. Eleven cases of primary hypophysitis and 2 cases of immunotherapy-related secondary hypophysitis were included. Of the 11 primary cases, 6 were diagnosed clinically without biopsy. Results: In primary hypophysitis, headache was the most common presenting symptom (6/11; 55%) and stalk enlargement the prevailing radiologic sign (8/11; 73%). Central adrenal insufficiency (4/11; 36%), central hypothyroidism (4/11; 36%), and central diabetes insipidus (CDI) (4/11; 36%) were the most common pituitary deficiencies at presentation. Initial management included surgery (4/11; 36%), supraphysiologic steroids (2/11; 18%), or observation (6/11; 55%). Outcomes assessed included radiologic improvement (8/9; 89%), improvement in mass symptoms (4/7; 57%), anterior pituitary recovery (1/7; 14%), and CDI recovery (0/4; 0%). In immunotherapy-related hypophysitis either under observation or supraphysiologic steroid therapy, the inflammatory mass resolved and pituitary dysfunction persisted. Conclusions: In primary hypophysitis, the inflammatory pituitary mass typically resolves and hypopituitarism persists. In the absence of severe or progressive neurologic deficits, a presumptive clinical diagnosis and conservative medical management should be attempted. In the absence of severe features, immunotherapy-related hypophysitis may be managed effectively without the use of supraphysiologic steroids.